Employment, Motherhood, and School Continuation Decisions of Young White, Black, and Hispanic Women - Ahituv, Avner; Tienda, Marta (Journal of Labor Economics, 2004)
We examine the empirical relationship between early employment activity and school continuation decisions for young American women using a dynamic, sequential discrete‐choice framework that estimates schooling, labor supply, and birth decisions jointly, controlling for unobserved heterogeneity and the endogeneity of these life cycle decisions. That the rate of school withdrawal increases as work intensity rises helps explain the higher departure rates of Hispanic girls from secondary school and the premature departure of young black women from college. The disturbing implication is that youth employment induces long‐run wage stagnation for early school leavers and potentially increases race and ethnic inequities.